Agronomic performance of white oats cultivated under fertigation with treated sewage effluent and definition of critical limits of Normalized Difference Vegetation Index - Coelho, Anderson Prates [UNESP] (2019)
One of the benefits of irrigation with wastewater in agriculture is the reduction in the use of mineral fertilizers and the increase in crop yield. For wastewater application, the use of remote sensing can help to define specific management areas. The aim of this study was to evaluate the yield and the growth of irrigated white oats (Avena sativa L.) with varying treated sewage effluent (TSE) levels. These attributes were then correlated with Normalized Difference Vegetation Index (NDVI) values obtained at four phenological stages of the crop and used to define critical limits of NDVI. The experiment consisted of five TSE treatments differing in irrigation depths (11, 31, 60, 87, and 100%). Mean NDVI values in the crop were determined with an active terrestrial sensor (GreenSeeker), which were then correlated with height, maximum leaf area index (LAI), panicles per square meter, number of grains per panicle, grain mass, grain yield (GY), and biomass yield (BY). In order to define the NDVI critical limits, NDVI values were generated as a function of relative BY in four phenological stages; NDVI values at 90% and 110% of relative BY were considered critical. Maximum GY (5.775 kg. ha(-1)) and BY (20,731 kg.ha(-1)) of white oats were achieved with TSE-induced nitrogen rates of 45 kg.ha(-1) and 88 kg. ha(-1), respectively. NDVI readings were highly correlated (greater than 0.85) with growth and yield of white oats. In this study, we defined the critical NDVI limits of white oats and obtained maximum precision at the phenological stage 10.5.4.